Effects of cementless fixation of implant prosthesis: A finite element study - Lee, Hyeonjong; Park, Soyeon; Kwon, Kung-Rock; Noh, Gunwoo (The journal of advanced prosthodontics, 2019)
A novel retentive type of implant prosthesis that does not require the use of cement or screw holes has been introduced; however, there are few reports examining the biomechanical aspects of this novel implant. This study aimed to evaluate the biomechanical features of cementless fixation (CLF) implant prostheses. The test groups of three variations of CLF implant prostheses and a control group of conventional cement-retained (CR) prosthesis were designed three-dimensionally for finite element analysis. The test groups were divided according to the abutment shape and the relining strategy on the inner surface of the implant crown as follows; resin-air hole-full (RAF), resin-air hole (RA), and resin-no air hole (RNA). The von Mises stress and principal stress were used to evaluate the stress values and distributions of the implant components. Contact open values were calculated to analyze the gap formation of the contact surfaces at the abutment-resin and abutment-implant interfaces. The micro-strain values were evaluated for the surrounding bone. Values reflecting the maximum stress on the abutment were as follows (in MPa): RAF, 25.6; RA, 23.4; RNA, 20.0; and CR, 15.8. The value of gap formation was measured from 0.88 to 1.19 µm at the abutmentresin interface and 24.4 to 24.7 µm at the abutment-implant interface. The strain distribution was similar in all cases. CLF had no disadvantages in terms of the biomechanical features compared with conventional CR implant prosthesis and could be successfully applied for implant prosthesis.